PERAN DAN KONSEKUENSI KEBIJAKAN MONETER DALAM EKONOMI SYARIAH - Riska Noviana; Ertanti Ardian; David Verdyansyah; Renny Oktafia (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Monetary policy is one of the crucial instruments in regulating the economy of a country. In conventional economics, monetary policy is implemented through mechanisms such as interest rates and open market operations. However, in Sharia-compliant economies, which are based on the prohibition of riba (interest), monetary policy must be executed using instruments that adhere to Sharia principles. This study adopts a literature review methodology, thus focusing on bibliographic materials by seeking relevant literature. The theoretical data utilized in this research is obtained from library literature and analyzed based on various references in this paper. By understanding the role and consequences of monetary policy in Sharia economics, it is hoped that new insights can be provided for the development and implementation of monetary policies that align with Sharia principles.